Integrative medicine
Integrative Medicine, by Dr. David Rakel, provides the practical, evidence-based guidance you need to safely and effectively integrate complementary and alternative medical treatments into your practice. This medical reference book lays the framework for making the best use of these therapeutic modalities and understanding the mechanisms by which these interventions work, keeping you at the forefront of the trend toward integrative health care